Rational design of imine‐linked three‐dimensional mesoporous covalent organic frameworks with bor topology. Issue 2 (28th March 2022) - Li, Zonglong; Hsueh, Chouhung; Tang, Zhuozhuo; Chen, Jia; Wang, Xiaolin; Cui, Hao; Yang, Yang; Wang, Xiaodan; Ren, Dongsheng; Gao, Hongqiang; Li, Mingyang; Xu, Hong; et al.
Abstract: Three‐dimensional (3D) covalent organic frameworks (COFs) possess great potential applications in various fields. Constructing 3D COFs with large pore sizes is extremely challenging due to the interpenetration and collapse. Herein, we report a series of crystalline imine‐linked 3D COFs (3D‐bor‐COF‐1, 3D‐bor‐COF‐2, 3D‐bor‐COF‐3) with mesoporous channels through rationally designing the topology configuration. These 3D‐bor‐COFs display permanent porosity and Brunauer–Emmett–Teller (BET) surfaces of 3205.5, 1752.7, and 2077.3 m 2 g −1 ( S Langmuir  = 4277.7, 2480.3, and 2698.0 m 2  g −1 ), respectively. The pore sizes of 3D‐bor‐COFs were confirmed by the lattice fringes from high‐resolution transmission electron microscopy, as well as structural simulation and nitrogen adsorption isotherm analysis. 3D‐bor‐COFs display large pore sizes (3.8 nm for 3D‐bor‐COF‐3), which is among the highest record of 3D COFs. Owing to the unstacked‐aromatic pore environment and high specific surface area, 3D‐bor‐COFs display excellent adsorption capacity for benzene vapor (1203.9 mg g −1 for 3D‐bor‐COF‐3) under 298 K, which is three times higher than that of the best‐reported 2D COF. This work not only provides inspiration for designing 3D mesoporous imine‐COFs, but also demonstrates a strategy for constructing aromatics adsorption materials. Abstract : With the high specific surface area, large pore volume, low density, and high stability, the three‐dimensional (3D) covalent organic frameworks (COFs) are one of the best options for exploring various fields. A series of mesoporous imine‐linked 3D COFs were prepared by reasonably selecting precursors and topology design. By virtue of mesoporous properties (3.8 nm for 3D‐bor‐COF‐3), the unstacked‐aromatic pore environment, and high BET (3205.5 m 2  g −1 for 3D‐bor‐COF‐1), 3D‐bor‐COFs display excellent adsorption capacity for benzene vapor (1203.9 mg g −1 for 3D‐bor‐COF‐3).